Challenges for the public relations' activity in the contemporary world: opinion survey with professionals from the state of Sao Paulo - Silva, Marcelo Pereira da; Trindade, Ana Carolina [UNESP]; Rossi, Jessica de Cassia (Univ Malaga, Inst Investigacion Relaciones Publicas, 2017)
The Public Relations activity carries a series of challenges considering teaching, learning and market. Through literary review and qualitative research, we introduce some historical elements of Public Relations and the adversities that the activity crossed by virtue of its authoritarian insertion in Brazil, shining a light on the connection between the education offered by the Institutions and the requirements of the market. From this article, we have noticed that some needs of the market trends for Public Relations arise from the historical gap between teaching and learning and the problems faced by the lack of affirmative policies of the profession through the class organs. We infer, consequently, that these aspects exalt the challenges and the opportunities related to the teaching of Public Relations, since in a country pervaded by corruption, Public Relations are gaining in the construction of a more just world through the truth.
Keywords: teaching; public relations; history; qualitative research; challenges